2012
DOI: 10.1590/s1516-89132012000400012
|View full text |Cite
|
Sign up to set email alerts
|

Influence of growth media and temperature on bacterial adhesion to polystyrene surfaces

Abstract: Bacterial adhesion to inert surfaces is a complex process influenced by environmental conditions. In this work, the influence of growth medium and temperature on the adhesion of Pseudomonas aeruginosa, Serratia marcescens, Staphylococcus aureus, Micrococcus luteus and Listeria monocytogenes to polystyrene surfaces was studied. Most bacteria demonstrated the highest adhesion when cultured in TSYEA, except S. marcescens, which showed to be positively influenced by the pigment production, favored in poor nutrient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 24 publications
3
32
0
Order By: Relevance
“…Under laboratorial conditions, Kadam et al 13 observed that nutrient availability affected biofilm formation by L. monocytogenes strains in polystyrene surfaces, highlighting that nutritionally poor media favored the growth in biofilm state. On the other hand, Zeraik and Nitschke 14 demonstrated that L. monocytogenes produced more biofilm in nutrient rich medium. In the present study, BHI broth was used because it has been reported as an effective medium to promote biofilm formation by L. monocytogenes isolates from different origins, at various surfaces 2, 15.…”
Section: Discussionmentioning
confidence: 99%
“…Under laboratorial conditions, Kadam et al 13 observed that nutrient availability affected biofilm formation by L. monocytogenes strains in polystyrene surfaces, highlighting that nutritionally poor media favored the growth in biofilm state. On the other hand, Zeraik and Nitschke 14 demonstrated that L. monocytogenes produced more biofilm in nutrient rich medium. In the present study, BHI broth was used because it has been reported as an effective medium to promote biofilm formation by L. monocytogenes isolates from different origins, at various surfaces 2, 15.…”
Section: Discussionmentioning
confidence: 99%
“…There was an increase (up to 50%; Table 2) in count for both groups of organisms, during the rainy season months of March to September but no significant difference (p > 0.05) was observed in the count of organisms between all months evaluated. It has been explained (Zeraik and Nitschke, 2012) that, environmental conditions can influence the complex process of bacterial adhesion to inert surfaces. Hence, the higher counts between March and September among the months analysed for microbial count (Table 2) may be due to, the prolonged period that the bottling equipment was kept idle which allowed microorganisms to proliferate.…”
Section: Resultsmentioning
confidence: 99%
“…The key non-enzymatic antioxidant -glutathione, both in reduced and oxidized forms, was found at highest level in the biofilm cells. The formation of bacterial biofilm on the surfaces of materials has been considered, with a few exceptions (Jayaraman et al 1997), as a highly undesirable processes (Geesey 2001;O'Toole 2003;MacKintosh et al 2006;Subramani et al 2009;Zeraik and Nitschke 2012). It is particularly undesirable for biomaterial surfaces exposed to a constant contact with the tissues and body fluids of living organism.…”
Section: Resultsmentioning
confidence: 99%